The risk assessment of loss due to landslides-cracks in the Tay Nguyen - Hung, Pham Van; Huyen, Nguyen Xuan (Vietnam Journal of Earth Sciences, 2015)
This work presents the initial results of the risk assessment of damage due to landslides caused cracks in the Tay Nguyen. Map damage risk Tay Nguyen area is built on the basis of integrated risk maps with maps cracked landslides hazard level under the socio-economic objects with spatial analysis in GIS. On the basis of analysis of synthetic risk maps for damage caused by landslides cracked Tay Nguyen region showed that the risk of damage due to accidents caused landslides cracked moderate - high. On the Tay Nguyen provinces, the risk level of damage caused by landslides crack distribution are very different. Area at risk of damage from landslides is very high and cracking high 21% area of the Tay Nguyen provinces, mainly along the Po river valley, river, Dong Nai and Ba River. Area at risk of damage from landslides cracked average accounted for 29% of the area of the Tay Nguyen; widely distributed in many parts of the Tay Nguyen region. Area at risk of damage caused by low soil cracks and very low loss accounted for 49,7% of the Tay Nguyen. Areas with high risk and very high damage of cities of Kon Tum, Pleiku, Buon Ma Thuot, Da Lat and Gia Nghĩa, towls of the district of Dak Glay, Ngoc Hoi, Dak To, Dak Ha, Ayun Pa, Krong Pa, An Khe, Duc Co, Chu Se, M'Drak, Krong Pak, Dak Lap, Don Duong, Bao Loc,... in the area above the local planning should be used rational use of territory and reasonable solution to prevent cracking landslides.ReferencesLê Mục Đích, 2001: Kinh nghiệm phòng tránh và kiểm soát tai biến địa chất. Nxb. Xây Dựng, Hà Nội (dịch từ tiếng Trung Quốc). Phạm Văn Hùng, Nguyễn Văn Dũng, 2013: Nghiên cứu đánh giá hiện trạng và cảnh báo nguy cơ nứt sụt đất ở khu vực Tây Nguyên. Tạp chí Các Khoa học về Trái đất, T.35, (3), tr.219-229. Nguyễn Trọng Yêm và nnk, 2006: Nghiên cứu xây dựng bản đồ tai biến môi trường tự nhiên lãnh thổ Việt Nam. Báo cáo tổng kết Đề tài cấp Nhà nước, mã số KC-08-01, lưu trữ Viện Địa chất, Hà Nội. Saaty, Thomas L. 1994: Fundamentals of decision making and priority theory with analytic hierarchy process. Pittsburgh: RWS publications, 527p.